Prenatal diagnosis of methylmalonic aciduria from amniotic fluid using genetic and biochemical approaches. (5th August 2019) - Ji, Xing; Wang, Huanhuan; Ye, Jun; Qiu, Wenjuan; Zhang, Huiwen; Liang, Lili; Xiao, Bing; Dai, Mengyao; Xu, Yan; Chen, Ting; Xu, Feng; Chen, Yingwei; et al.
Abstract: Objectives: This study reported the clinical prenatal diagnosis experience of families affected by methylmalonic acidemia (MMA) evaluated at a single prenatal diagnosis center over 8 years, and the reliability of a biochemical approach for prenatal diagnosis was analyzed. Methods: Prenatal diagnosis data for 187 MMA families referred to our center from 2009 to 2016 were reviewed retrospectively. The results of the genetic analysis and biochemical approach were compared. Results: A total of 41 MMA‐affected pregnancies (21%) were identified. The biochemical analysis could identify the true status of 99.5% of fetuses. The diagnostic sensitivities of the propionylcarnitine (C3) level, the C3 to acetylcarnitine (C2) ratio (C3/C2), the methylmalonic acid, and methylcitrate levels in the amniotic fluid were 95.1%, 100%, 100%, and 82.9%, respectively, and the specificities were 98.7%, 99.3%, 97.4%, and 96.7%, respectively. Conclusions: The biochemical analysis could be optionally used in the prenatal diagnosis of MMA, especially in cases where the genetic results are inconclusive. Among the four tested biochemical markers, C3/C2 appeared to be the most reliable.